An Enhanced Distributed Accountability for Data Sharing in the Cloud Computing Technologies - Kumar, Komuravelly Sudheer; Chythanya, K Ravi; Kumar, N Vijay; Siruvoru, Vahini (International Journal of Engineering and Technology, 2018)
In the fast growing world the cloud services benefit the humankind in several ways to ease the processing of a distance computers to communicate and storage. Having several advantages there are few chances of losing control their individual data became tuff job to the cloud service providers. To alleviate this, in this paper there is implementation of data accountability scheme that regularly track the data in the cloud of every user with the help of JAR file system for providing user authenticity. However every user can upload their individual data to cloud and can obtain one account on their own which supports the encrypted format and when the user requires his/her data.